1989
DOI: 10.1038/341060a0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct antigen receptor repertoires of two classes of murine epithelium-associated T cells

Abstract: T lymphocytes are found not only as recirculating cells in the lymphoid system, but also as immobile cells in certain epithelia. T-cell antigen receptors (TCR) of both alpha/beta and gamma/delta-heterodimer subtypes can exhibit an extremely high degree of diversity. The diversity of alpha/beta TCRs derives from the use of a large number of variable (V) gene segments, as well as junctional diversity generated during rearrangement of these segments, whereas the diversity of gamma/delta TCRs derives largely from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(126 citation statements)
references
References 29 publications
4
122
0
Order By: Relevance
“…Because fetal thymocytes expressing V␥5-bearing TCRs were previously reported to be precursors of DETCs (10,18,39,40), we first examined the development of fetal thymocytes in V␦1 Ϫ/Ϫ mice. The development of ␥␦TCR ϩ and V␥5 ϩ fetal thymocytes of V␦1 Ϫ/Ϫ mice was markedly impaired during the early-middle fetal period (GD15-GD18); thereafter, the number of ␥␦TCR ϩ , but not V␥5 ϩ , thymocytes recovered in newborn mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because fetal thymocytes expressing V␥5-bearing TCRs were previously reported to be precursors of DETCs (10,18,39,40), we first examined the development of fetal thymocytes in V␦1 Ϫ/Ϫ mice. The development of ␥␦TCR ϩ and V␥5 ϩ fetal thymocytes of V␦1 Ϫ/Ϫ mice was markedly impaired during the early-middle fetal period (GD15-GD18); thereafter, the number of ␥␦TCR ϩ , but not V␥5 ϩ , thymocytes recovered in newborn mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TCR-V␥/V␦ repertoire is diverse in ␥␦TCR ϩ IEL, the ␥␦TCRs expressed by small intestinal IEL consist predominantly of TCR-V␥1 or -V␥5 paired with TCR-V␦4, -V␦5, -V␦6, or -V␦7 (33,34). To assess whether there were any differences in the TCR-V␥/V␦ repertoire of ␥␦TCR ϩ IEL in small intestine, we analyzed ␥␦TCR ϩ IEL in CCR9 Ϫ/Ϫ and CCR9 ϩ/ϩ mice for the expression of TCR-V␥1, -V␥2, -V␥5, and -V␦4 by flow cytometry.…”
Section: Abnormal Distribution Of ␥␦Tcrmentioning
confidence: 99%
“…Altogether, these data suggested that IL-15 responses by the developing IEL by means of transpresentation of IL-15 by parenchymal cells was the major mechanism of IL-15-mediated IEL development. (18,(20)(21)(22). We wanted to determine whether TCR␥␦ IEL with different V␥ usage were equally affected by IL-15R␣ deficiency.…”
Section: Parenchymal Cell Expression Of Il-15r␣ and Il-15 But Not Ilmentioning
confidence: 99%